Utilization of YouTube Videos as Learning Media in the Mass of the Covid 19 Pandemic in the History of Islamic Culture for Class XII Students - ziaulhaq, wahyuziaulhaq (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This study describes the use of YouTube videos as learning media in the Covid-19 pandemic mass in the history of Islamic culture in class XII students. The purpose of this research is to educate readers that during the COVID-19 pandemic, learning activities are not carried out face-to-face but utilize digital technology to break the chain of transmission of Covid 19 through YouTube videos. The research method used is qualitative. The approach used is anthropological and sociological. Data collection techniques are through observation and unstructured interviews, after the data is obtained, the data is analyzed scientifically. The results of the research that have been found show that. First, YouTube videos are the right media to be used as a source of teaching materials for the COVID-19 masses so that students can study at home. Second, youtube shows are easily accessible by students. Third, YouTube shows are packaged in interesting and easy-to-understand languages ​​for students and are held for 30 minutes.